Relative and Cross-national Human Resource Management research: Development of a hypothetical model (Global Journal of Management and Business Research, 2012)
Rapid development of the human resource management (HRM) discipline has been discussed in this article with the need for more cross-national HRM studies. Thereafter the universal applicability of Anglo-Saxon models of HRM is questioned. In order to examine the applicability of HRM models in various settings (national and international), six major HRM models have been critically analyzed and their main research propositions have been identified. This provides the foundation for a framework for HRM evaluations in diverse contexts. Based on such a framework and developments in the literature, finally, a contextual model is proposed for conducting cross-national and relative HRM studies. The paper also provides some related directions for future research also.
Keywords: Human Resource Management; HRM models; HRM contextual framework; Cross-national research; HRM developments